Molecular dynamics study of Desulfovibrio africanus cytochrome c3 in oxidized and reduced forms. - Bret, Céline (2002)
A 5-ns molecular dynamics study of a tetraheme cytochrome in fully oxidized and reduced forms was performed using the CHARMM molecular modeling program, with explicit water molecules, Langevin dynamics thermalization, Particle Mesh Ewald long-range electrostatics, and quantum mechanical determination of heme partial charges. The simulations used, as starting points, crystallographic structures of the oxidized and reduced forms of the acidic cytochrome c(3) from Desulfovibrio africanus obtained at pH 5.6. In this paper we also report structures for the two forms obtained at pH 8. In contrast to previous cytochrome c(3) dynamics simulations, our model is stable. The simulation structures agree reasonably well with the crystallographic ones, but our models show higher flexibility and the water molecules are more labile. We have compared in detail the differences between the simulated and experimental structures of the two redox states and observe that the hydration structure is highly dependent on the redox state. We have also analyzed the interaction energy terms between the hemes, the protein residues, and water. The direct electrostatic interaction between hemes is weak and nearly insensitive to the redox state, but the remaining terms are large and contribute in a complex way to the overall potential energy differences that we see between the redox states.